The effect of intradialytic virtual reality on reducing anxiety and depression in chronic kidney disease patients on hemodialysis - Nieniek Ritianingsih; Farial Nurhayati; Asep Kuswandi; Lia Herliana (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Patients with chronic kidney disease (CKD) undergoing hemodialysis often experience physical and psychological problems, including anxiety and depression, due to disease progression and its complications. Intradialytic virtual reality (VR) exercise is a non-pharmacological intervention that uses immersive three-dimensional technology to distract patients and potentially reduce psychological distress. Objective: To examine the effect of intradialytic VR on anxiety and depression levels in CKD patients undergoing hemodialysis. Methods: This quantitative study used a quasi-experimental pretest–posttest control group design and was conducted at PMI Hospital, Bogor, in 2025. A total of 76 respondents were recruited using purposive sampling and divided equally into intervention and control groups (38 each). Inclusion criteria were adult hemodialysis patients who were cooperative, hemodynamically stable, and willing to participate. Patients with complications or unstable conditions were excluded. The intervention group received intradialytic VR twice weekly for 4 weeks. Anxiety and depression were assessed using the Depression Anxiety Stress Scale (DASS). Data were analyzed using dependent and independent t-tests. Results: Intradialytic VR significantly reduced anxiety and depression levels in the intervention group compared with the control group (p=0.0001). The mean post-intervention difference between groups was 10.77 for anxiety and 10.03 for depression. Conclusion: Intradialytic VR is a promising nursing intervention for reducing anxiety and depression in hemodialysis patients with psychosocial problems.